Evolution of MALDI-TOF MS Profiles from Lice and Fleas Preserved in Alcohol over Time - Hanene Benyahia; Philippe Parola; Lionel Almeras (Insects, 2023)
MALDI-TOF is now considered a relevant tool for the identification of arthropods, including lice and fleas. However, the duration and conditions of storage, such as in ethanol, which is frequently used to preserve these ectoparasites, could impede their classification. The purpose of the present study was to assess the stability of MS profiles from Pediculus humanus corporis lice and Ctenocephalides felis fleas preserved in alcohol from one to four years and kinetically submitted to MALDI-TOF MS. A total of 469 cephalothoraxes from lice (n = 170) and fleas (n = 299) were tested. The reproducibility of the MS profiles was estimated based on the log score values (LSVs) obtained for query profiles compared to the reference profiles included in the MS database. Only MS spectra from P. humanus corporis and C. felis stored in alcohol for less than one year were included in the reference MS database. Approximately 75% of MS spectra from lice (75.2%, 94/125) and fleas (74.4%, 122/164) specimens stored in alcohol for 12 to 48 months, queried against the reference MS database, obtained relevant identification. An accurate analysis revealed a significant decrease in the proportion of identification for both species stored for more than 22 months in alcohol. It was hypothesized that incomplete drying was responsible for MS spectra variations. Then, 45 lice and 60 fleas were subjected to longer drying periods from 12 to 24 h. The increase in the drying period improved the proportion of relevant identification for lice (95%) and fleas (80%). This study highlighted that a correct rate of identification by MS could be obtained for lice and fleas preserved in alcohol for up to four years on the condition that the drying period was sufficiently long for accurate identification.